2013
DOI: 10.1175/jpo-d-12-0178.1
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Eddy Fluxes in the Southern Ocean

Abstract: The overturning circulation of the Southern Ocean has been investigated using eddying coupled ocean-sea ice models. The circulation is diagnosed in both density-latitude coordinates and in depth-density coordinates. Depth-density coordinates follow streamlines where the Antarctic Circumpolar Current is equivalent barotropic, capture the descent of Antarctic Bottom Water, follow density outcrops at the surface, and can be interpreted energetically. In density-latitude coordinates, wind-driven northward transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 31 publications
1
51
0
Order By: Relevance
“…Finally, standing meanders distort the front meridionally, increasing the surface of exchange at the front. These ideas have been hypothesized or discussed in several recent studies, which all tend to show that eddy activity is augmented in the presence of standing meanders (Naveira Garabato et al 2011; Thompson and Sallée 2012;Zika et al 2013;Abernathey and Cessi 2014). In particular, using numerical simulations with and without topography, Abernathey and Cessi (2014) showed that cross-frontal eddy heat flux was stronger in the experiment with topography due to the presence of standing meanders.…”
Section: ) Hotspots Of Tracer Transportmentioning
confidence: 83%
“…Finally, standing meanders distort the front meridionally, increasing the surface of exchange at the front. These ideas have been hypothesized or discussed in several recent studies, which all tend to show that eddy activity is augmented in the presence of standing meanders (Naveira Garabato et al 2011; Thompson and Sallée 2012;Zika et al 2013;Abernathey and Cessi 2014). In particular, using numerical simulations with and without topography, Abernathey and Cessi (2014) showed that cross-frontal eddy heat flux was stronger in the experiment with topography due to the presence of standing meanders.…”
Section: ) Hotspots Of Tracer Transportmentioning
confidence: 83%
“…An Eulerian zonal average of the meridional flow yields a strong Deacon cell (Döös and Webb 1994), which bears little resemblance to tracer pathways. We therefore analyze the physical circulation in latitude-density space, which can be written [following Zika et al (2013)] as…”
Section: Overturning Diagnosticsmentioning
confidence: 99%
“…This diagnostic is computed online during the simulation. The depth-density streamfunction, again following Zika et al (2013), is written as…”
Section: Overturning Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its consequent steeply sloping isopycnals connect a huge fraction of the deep ocean to the atmosphere (Rintoul et al 2001;Johnson and Bryden 1989). Turbulent processes, themselves intimately linked to the ACC, play a major role in exchanges between near-surface waters and the ocean interior (Marshall 1997;Zika et al 2013). Knowledge of what drives the ACC is thus critical to our understanding of ocean circulation and climate.…”
Section: Introduction: the Accmentioning
confidence: 99%